2012
DOI: 10.1159/000335154
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s Disease in the Retina: Imaging Retinal Aβ Plaques for Early Diagnosis and Therapy Assessment

Abstract: Background: Definite Alzheimer’s disease (AD) diagnosis at early stages is vital for targeting intervention, yet currently unavailable. Noninvasive detection of the pathological hallmark, amyloid-β protein (Aβ) plaques, is limited in the brain. However, the existence of Aβ plaques in the retina, possibly at presymptomatic stages, may improve early detection of AD. Objective: To summarize clinical and preclinical evidence showing that the retina, an accessible part of the central nervous system, displays abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
167
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 183 publications
(179 citation statements)
references
References 207 publications
(142 reference statements)
7
167
2
3
Order By: Relevance
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…In line with the above findings, numerous studies examining the retinas of sporadic and transgenic animal models of AD have reported Aβ deposits, vascular Aβ, pTau, and paired helical filament-tau (PHF-tau), often in association with RGC degeneration, local inflammation (i.e., microglial activation), and impairments of retinal structure and function (11,39,40,42,(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61). These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57).…”
Section: Introductionmentioning
confidence: 57%
“…These studies, which included a variety of transgenic rat and mouse models, as well as the sporadic rodent model of AD, Octodon degus, demonstrated abundant Aβ deposits, mainly in the innermost retinal layers (RGCs and NFL) (40,42,45,49,52,54,57). Furthermore, several publications, including ours, have reported a positive response to therapy in reducing retinal Aβ plaque burden in transgenic (ADtg) murine models, often reflecting the reaction observed in the respective brains (40,48,51,52,56,60). To visualize retinal Aβ pathology in vivo, we had previously developed a noninvasive retinal amyloid imaging method for rodent ADtg models, using curcumin as a contrast agent (40,51).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Notably, psychophysical exploration of the parvocellular pathway are affected in AD. 4,5 Our data showed values for the macular RNFL thickness and total macular volume measured by OCT to have highly significant sensitivity and specificity for differentiating mild AD patients from healthy subjects. The most sensitive area was the superior inner macula, followed by the temporal inner macula, with ROCs values of 85% and 80%, respectively.…”
mentioning
confidence: 74%
“…These factors might also help to explain why Aβ aggregates are mainly deposited in the brain and cerebral vessel walls, and only rarely in peripheral organs (although detection of Aβ aggregates has been claimed in skin, subcutaneous tissue, intestinal tissues, and heart) [13][14][15] . The aggregation (oligomerization and fibrillogenesis) of Aβ peptides is determined by the relative proportions of Aβ species, their concentrations, the pH, temperature and ionic strength of solution, and incubation time 16 .…”
mentioning
confidence: 99%